Study on effects of preparation method on the structure and antioxidant activity of protein-Tremella fuciformis polysaccharide complexes by asymmetrical flow field-flow fractionation. (1st August 2022) - Chen, Xue; Tian, Yiling; Zhang, Jie; Li, Yueqiu; Zhang, Wenhui; Zhang, Jing; Dou, Yuwei; Dou, Haiyang
Highlights: Low density lipoprotein-Tremella fuciformis polysaccharide complexes were prepared. Effect of the preparation method on the structure of the complex was investigated. Field-flow fractionation was employed for the characterization of the complex. The antioxidant activity of the complex was studied. Abstract: Oxidation is an essential biological process for human life. In this study, low density lipoprotein- Tremella fuciformis polysaccharide (LDL-TFP) complexes were prepared by electrostatic and covalent methods. The effects of preparation method on the structure and antioxidant activity of LDL-TFP complexes were investigated by asymmetrical flow field-flow fractionation (AF4) coupled with ultraviolet–visible (UV/Vis), multiangle light scattering (MALS), and differential refractive index (dRI) detectors. The results showed that the electrostatic LDL-TFP complexes had a spherical structure, while the covalent LDL-TFP complexes had a rod-like structure as indicated by the ratio of R g (radius of gyration) to R h (hydrodynamic radius). Moreover, the results revealed that the antioxidant activity of the LDL-TFP complexes on the HepG2 could be related to the structure of LDL-TFP complexes. The antioxidant activity of LDL-TFP complexes formed by LDL modified with phospholipase A2 was further enhanced. This study would help expand the application of TFP.